PKM IMPLEMENTASI STRATEGI MENGELOLA SUMBER DAYA MANUSIA (SDM) ERA 5.0 DALAM TATANAN NORMAL BARU BAGI PELAKU UMKM DI KECAMATAN CINERE KOTA DEPOK - Renny Husniati; Syarif Ali; Yudi Nur Supriadi; Iwan Kresna (LPPM Universitas Bina Bangsa, 2022)
After being designated as a pandemic, Covid-19 has made us inevitably change our lifestyle and work patterns from the previous normal conditions. The results of the LIPI survey show that after the Covid-19 pandemic, as many as 95% of MSMEs experienced the impact of this pandemic, and there were around 75% of the MSME sector that experienced a significant decline in income as a result of the pandemic. Counseling on strategies for managing superior human resources in the new normal order for MSME actors in Cinere District has a special goal, namely it is hoped that participants in this community service activity will be able to adapt to the challenges of the new normal so that they can maintain the existence of their UMKM business and increase their business productivity. The industrial revolution 4.0 which is characterized by the widespread use of Information Technology such as the use of artificial intelligence is an opportunity and threat to the business world. However, as the wave of industry 5.0 enters, humans become a central point to attract the greatest benefit to the use of technology, the main prerequisite that must be met is that business people have a link-and-match thinking pattern with the aim of creating technology. The problem of MSME players is still shackled with the old mindset, seeking profit or success, for the short term, this kind of mindset is not suitable for pursuing the flow of industry 5.0. In addition to being able to take advantage of technology, awareness to apply universal values is important to be upheld, therefore PKM activities emphasize more on strengthening the character values of MSME actors. The implementation method is carried out using the Kurt Lewin model approach. In addition, the methods used are lectures, questions and answers, brain games, distribution of materials, with the target group of MSME actors in Cinere district, Depok